STRATEGI PEMERINTAH DALAM PENGEMBANGAN UMKM DI KABUPATEN JEPARA - Khoirul Anam; Sulistyowati . (Journal of Politic and Government Studies, 2019)
There is a policy strategy from the Jepara Regency Government to help solve three classic problems that often hit MSMEs, namely market access, capital, and technology which have often been discussed at seminars or conferences. So that this study aims to analyze the government's strategy in the development of MSMEs and describe government obstacles in the implementation of MSME development strategies in Jepara District. For this reason, the author analyzes using the model theory and dimensions of Muhammad Suwarsono's governance strategy, as well as the theory of the government's role in developing MSMEs by Gede Diva. The results of this study are what are the strategies carried out by the Jepara District Government in developing MSMEs, as well as obstacles in the implementation of MSME development strategies in Jepara Regency.This study used descriptive qualitative method. This type of descriptive research is a problem solving procedure that is examined by describing the subject / object of research in accordance with the facts and about an ongoing process in the field. In obtaining data, researchers conducted interviews with the Office of Cooperative and Small and Medium Enterprises and Transmigration, and MSME actors. The results of the research that has been carried out are that the strategy is incremental (always increasing) aimed at pursuing high economic growth, employment, increasing competitiveness and poverty reduction and including developing environmentally friendly businesses. As well as the obstacles experienced are lack of human resources, budget, facilities and infrastructure.Suggestions from the authors for the Jepara Regency Government especially the UKM Cooperative and Transmigration Office are to increase the budget for the implementation of MSME development strategies and to add personnel or members of the SME Cooperative and Transmigration Cooperative Office field especially in the SME Sector so that the strategy can be maximized.Keywords: Jepara MSMEs, development strategies, business people, strategy implementation